GE_GERICHTE P/14716/2021 vom 28. Juli 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ASSISTANCE JUDICIAIRE;MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP) | CPP.310.al1.leta; CP.129